Genotype-Specific Response to Silicon Supply in Young Tomato and Unripe Melon Plants Grown in a Floating System - Annalisa Somma; Onofrio Davide Palmitessa; Massimiliano D’Imperio; Francesco Serio; Pietro Santamaria (Horticulturae, 2024)
Agronomic biofortification of crops is a promising approach for the accumulation of Si in plant organs and can be achieved through the application of Si-containing fertilizers in the nutrient solution (NS) using a soilless technique. In the present research, a local variety of Cucumis melo L. called Carosello and two tomato hybrids, ‘Alfa 200’ (TA) and ‘Versus’ (TV), were cultivated in a floating system with three levels of Si (0, 50, and 100 mg·L−1) in the NS with the aim to study the Si translocation/accumulation in leaves, stems, and roots of these genotypes. In general, by adding Si to the NS, Si accumulation in plants increased. Regarding Si translocation, it was found that Carosello exhibited a better translocation capacity than tomato hybrids, and Si movement from roots to shoots was very much dependent on tomato genotypes. With the highest Si content in the NS, TA had a similar Si concentration in leaves and stems, while TV showed a greater Si concentration in leaves. In conclusion, Carosello landrace is confirmed as a good Si accumulator, while the tomato is confirmed as a species with low Si accumulation capacity. Nevertheless, the effectiveness of Si biofortification in tomatoes is very much dependent on the genotype.